2012
DOI: 10.1152/physiolgenomics.00170.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mononuclear cells induce beneficial remodeling and reduce diastolic dysfunction in the left ventricle of hypertensive SS/MCWi rats

Abstract: Little is known about the effectiveness of BMMNC therapy in hypertensive heart disease. In the current study, we show that delivery of BMMNCs from hypertension protected SS-13 BN /MCWi donor rats, but not BMMNC from hypertension susceptible SS/MCWi donor rats, resulted in 57.2 and 83.4% reductions in perivascular and interstitial fibrosis, respectively, as well as a 60% increase in capillary-to-myocyte count in the left ventricles (LV) of hypertensive SS/MCWi recipients. These histological changes were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…After day 3 of culture, nonadherent cells were removed and new media were provided, with subsequent medium changes every 3 days until day 10 -14 or when plated cells reached Ďł60% confluence. Previous characterization of this BM-EPC population under the same isolation and growth conditions by our laboratory (data not shown) indicated that Ďł90% of the cells are positive for a panel of markers including VEGFR2, CD34, CD133, cKIT, and Ac-LDL (16,50). Additionally, throughout this study, we utilize conditions of standard cell culture normoxia (20% O 2) and hypoxia (2% O2) shown to regulate VEGFRs at the cell surface (39), which can vary in vivo depending on the subset of vessels.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…After day 3 of culture, nonadherent cells were removed and new media were provided, with subsequent medium changes every 3 days until day 10 -14 or when plated cells reached Ďł60% confluence. Previous characterization of this BM-EPC population under the same isolation and growth conditions by our laboratory (data not shown) indicated that Ďł90% of the cells are positive for a panel of markers including VEGFR2, CD34, CD133, cKIT, and Ac-LDL (16,50). Additionally, throughout this study, we utilize conditions of standard cell culture normoxia (20% O 2) and hypoxia (2% O2) shown to regulate VEGFRs at the cell surface (39), which can vary in vivo depending on the subset of vessels.…”
Section: Methodsmentioning
confidence: 62%
“…BM-EPCs were isolated from Sprague-Dawley (SD) rat (Harlan) hind limbs according to these approved protocols. Bone marrow isolation (50), BM-EPC culture in MCDB131 basal media (US Biologicals) plus 10% FBS (GIBCO by Invitrogen) and EGM-2 supplement packs (Lonza), and phenotypic verification were performed as previously described (16,50). Using a set of accepted growth conditions (20), we plated approximately five million isolated primary bone marrow mononuclear cells (16) per bovine fibronectin-coated (10 g/ml) 100 mm plate.…”
Section: Methodsmentioning
confidence: 99%
“…SD donor rats were placed on a normal-salt diet (NSD; 0.4% NaCl Dyets) or a high-salt diet (HSD; 4% NaCl Dyets) for 7 days before cell isolation. Donor rats were killed with an overdose of beuthanasia, and their BM-MNCs were harvested as previously described (14,42). Briefly, bone marrow was harvested from the tibias and femurs by flushing with MCDB131 (E3000-01B; US Biologicals) with 5% heat-inactivated fetal bovine serum (FBS; GIBCO by Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…EPC transplantation also increased microvessel density and decreased fibrosis in cardiac tissue in a salt‐sensitive hypertensive rat model, by increasing blood flow and an improving diastolic function (Parker et al. ). Under some experimental conditions EPCs can incorporate into blood vessels (Yeh et al.…”
Section: Introductionmentioning
confidence: 99%